Two New β3 Integrin Mutations in Indian Patients with Glanzmann Thrombasthenia: Localization of Mutations Affecting Cysteine Residues in Integrin β3 - Nair, Sona; Li, Jihong; Mitchell, W. Beau; Mohanty, Dipika; Coller, Barry S.; French, Deborah L. (Thrombosis and Haemostasis, 2002)
New mutations in the β3 integrin subunit have been identified in two unrelated Glanzmann thrombasthenia patients originating from India and Bangladesh. Both patients had histories of excessive bleeding and were found to have Glanzmann thrombasthenia based on absent ADPinduced platelet aggregation. Immunoblotting of platelet lysates of Patient 1 demonstrated reduced levels of αIIb and an unexpected high Mr β3 band of ∼260,000, with little or no normal-sized β3. Upon reduction, a weak β3 band of normal Mr was observed. Platelet lysates of Patient 2 demonstrated undetectable levels of β3. Sequence analyses identified homozygous mutations in the β3 genes of both patients. Patient 1 had a C506Y missense mutation resulting in the expression of an unpaired cysteine; we propose that the Mr ∼260,000 band is a disulfide-bonded β3 dimer. Patient 2 had an insertion mutation resulting in a frameshift and premature termination. Both mutations affect biogenesis of platelet αIIbβ3 receptors.This work was supported in part by grants HL19278 (B.S.C.), AHA Heritage Affiliate, Ilma F. Kern Foundation in honor of Jonathan Halperin, MD (D.L.F.), The Charles Slaughter Foundation (D.L.F.), and a fellowship from an Institutional NRSA, NHLBI T32 HL07824-06 (to W.B.M.)
Keywords: Platelets; αIIbβ3; Glanzmann thrombasthenia